2017
DOI: 10.1136/tobaccocontrol-2017-053639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plain packaging of cigarettes on the risk perception of Uruguayan smokers: an experimental study

Abstract: Plain packaging enhanced the perceived risk of cigarette products even in a highly regulated setting such as Uruguay. Both the elimination of distinctive brand elements and the use of Australia's dark brown background colour contributed to the observed effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
2
4
0
1
Order By: Relevance
“…From the viewpoint of the second persona, who operates under the constraints of addiction, color becomes a product attribute within a rational set of preference rules over cigarette packages. Here, we confirmed the findings of numerous other studies that smokers' perceptions of risk are in fact influenced by package colors (Hammond et al 2014, Wakefield, Germain, and Durkin 2008, Bansal-Travers et al 2011, Doxey and Hammond 2011, Harris et al 2017. percent.…”
Section: How Can Addicted Smokers Be Rational?supporting
confidence: 91%
See 2 more Smart Citations
“…From the viewpoint of the second persona, who operates under the constraints of addiction, color becomes a product attribute within a rational set of preference rules over cigarette packages. Here, we confirmed the findings of numerous other studies that smokers' perceptions of risk are in fact influenced by package colors (Hammond et al 2014, Wakefield, Germain, and Durkin 2008, Bansal-Travers et al 2011, Doxey and Hammond 2011, Harris et al 2017. percent.…”
Section: How Can Addicted Smokers Be Rational?supporting
confidence: 91%
“…Other experimental studies and cross-sectional surveys have supported the conclusion that lighter package colors are perceived as more healthful (Hammond et al 2014, Wakefield, Germain, and Durkin 2008, Bansal-Travers et al 2011, Doxey and Hammond 2011. In an earlier discrete choice experiment (Harris et al 2017), we found that a package with a white background and a blue stripe was perceived as less risky.…”
Section: Parametric Modelssupporting
confidence: 71%
See 1 more Smart Citation
“…While experimental research has shown that standardised packaging can strengthen the impact of large health warnings (e.g. Andrews et al 2016;Harris et al 2018), as our question about thoughts of quitting specifically asks about the look of the pack it is not possible to separate the impact of the warnings from the removal of full branding. Researchers in Australia similarly concluded that their findings must be considered the result of all the changes to the packaging (White et al 2015), consistent with the view of marketers, that the 'overall effect of the package comes not from any individual element but rather from the gestalt of all elements working together as a holistic design' (Orth and Malkewitz 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Otros buscan dar mensajes a los consumidores asociados a salud, modernidad o vitalidad. Esto ha sido particularmente dirigido a la población joven, pudiendo ser los cigarrillos saborizados una forma atractiva de ini-ciarlos en el consumo (18)(19)(20) , aumentar la adictividad (21) , disminuir la percepción de riesgo, lo que ha sido también estudiado en nuestro medio (22) . Los efectos refrescantes, analgésicos y relajantes en la garganta y la boca del mentol, uno de los principales aditivos asociados al tabaco, reducen los efectos irritantes y molestos de la nicotina y, así, facilitan el acto de fumar (23) .…”
Section: Introductionunclassified